Prevention of Escherichia coli K1 Penetration of the Blood-Brain Barrier by Counteracting the Host Cell Receptor and Signaling Molecule Involved in E. coli Invasion of Human Brain Microvascular Endothelial Cells - Zhu, Longkun (American Society for Microbiology (ASM), 2010)
Escherichia coli meningitis is an important cause of mortality and morbidity, and a key contributing factor is our incomplete understanding of the pathogenesis of E. coli meningitis. We have shown that E. coli penetration into the brain requires E. coli invasion of human brain microvascular endothelial cells (HBMEC), which constitute the blood-brain barrier. E. coli invasion of HBMEC involves its interaction with HBMEC receptors, such as E. coli cytotoxic necrotizing factor 1 (CNF1) interaction with its receptor, the 67-kDa laminin receptor (67LR), and host signaling molecules including cytosolic phospholipase A(2)α (cPLA(2)α). In the present study, we showed that treatment with etoposide resulted in decreased expression of 67LR on HBMEC and inhibited E. coli invasion of HBMEC. Pharmacological inhibition of cysteinyl leukotrienes, lipoxygenated products of arachidonic acid released by cPLA(2)α, using montelukast (an antagonist of the type 1 cysteinyl leukotriene receptor) also inhibited E. coli invasion of HBMEC. E. coli penetration into the brain was significantly decreased by etoposide as well as by montelukast, and a combination of etoposide and montelukast was significantly more effective in inhibiting E. coli K1 invasion of HBMEC than single agents alone. These findings demonstrate for the first time that counteracting the HBMEC receptor and signaling molecule involved in E. coli invasion of HBMEC provides a novel approach for prevention of E. coli penetration into the brain, the essential step required for development of E. coli meningitis.